Age‐ and disease‐specific reference values for neurofilament light presented in an online interactive support interface. Issue 11 (5th October 2022) - Vermunt, Lisa; Otte, Marco; Verberk, Inge M. W.; Killestein, Joep; Lemstra, Afina W.; van der Flier, Wiesje M.; Pijnenburg, Yolande A. L.; Vijverberg, Everard G. B.; Bouwman, Femke H.; Gravesteijn, Gido; van de Berg, Wilma D. J.; Scheltens, Philip; et al.
Abstract: Interpretation of axonal damage biomarker Neurofilament Light chain (NfL) concentrations is difficult due to the lack of age‐specific and disease‐specific reference values. We here developed an interactive interface to support interpretation of NfL results in human body fluids. We used NfL values of 1698 individuals without a neurological disorder, aged 19–85 years, and patients with MS and dementias. Percentile regression estimates per diagnosis populate interactive graphs, alongside NfL background information (available on: https://mybiomarkers.shinyapps.io/Neurofilament ). This accessible interface provides reference for interpretation of the individual patient results for clinicians. It showcases an adaptable method to support interpretation of age‐dependent biomarkers in neurology.